Distinct Patterns of Urban-Rural and Sex Disparities in Children's BMI Trajectories From 2013 to 2018 - Zhou, Yunping; Yu, Pengli; Zhang, Yanqing; Wang, Tao; Wang, Aimin (Frontiers in Public Health, 2021)
Background: To identify distinct trajectories of body mass index (BMI) in a large sample of Chinese children by urban-rural and sex. Methods: Data for this study was obtained from the National Surveys on Chinese Students’ Constitution and Health among 16 060 children aged 6-11 years. Weight and height data were used to calculate BMI. The group-based trajectory modeling (GBTM) was used to identify distinct BMI trajectories. Results: Seven distinct trajectories were identified, “Sustained Healthy Weight (46.01%)”, “Sustained Obesity (17.26%)”, “Sustained Underweight (4.50%)”, “Obesity to Overweight (6.45%)”, “Obesity to Healthy Weight (11.75%)”, “Healthy Weight to Overweight (8.67%)”, and “Healthy Weight to Obesity (5.36%)”. The proportions of “Sustained Obesity”, “Healthy Weight to Obesity” and “Healthy Weight to Overweight” trajectories were much higher among boys compared with girls (P<0.001). Meanwhile, children living in rural areas were more represented in the “Healthy Weight to Obesity” trajectory (P<0.001). Conclusion: In this study, the proportions of BMI development trajectories among 6-11 years children varied by sex and urban-rural areas, which may require tailored interventions specifically towards these at-risk trajectories.